PERBANKAN DAN KEUANGAN SYARIAH DI INDONESIA: PELUANG DAN TANTANGAN DI ERA DIGITAL - Sapitriani, Anriya; Ananda, Bethi Risqi; Syaputra, Lianar; Restie, Maria; Salsabila, Alifa (Jurnal Ekonomi & Bisnis, 2024)
This journal discusses the challenges and opportunities faced by Islamic banks in the digital era, with the aim of analyzing how Islamic banks can take advantage of existing opportunities while overcoming the challenges that arise due to digital developments. The research method used is qualitative with a literature study approach, which includes collecting, reviewing and analyzing relevant literature such as books, journal articles, research reports and official documents. The research results show that Islamic banks face challenges in the digital era, including the need for quality human resources, consumer protection, cyber security, and increasing public financial literacy. However, the digital era also opens up great opportunities for Islamic banks to improve operational efficiency, expand market reach and offer innovative services. To face the digital era, Islamic banks need to implement strategies to increase workforce skills, utilize digital technology, implement supportive regulations, and innovate through startup development. The transformation towards digital banking allows Islamic banks to remain competitive and relevant amidst technological advances, ensuring customer needs are met in a fast and practical way.